An exploration of sight, and its relationship with reality, in literature from both world wars - Hodges, E; Elizabeth Hodges (2013)
Writers from both world wars, concerned with the representation of war, wrestled with the predicament of partial sight. Their work reveals the problematic dichotomy that exists between the individual’s selective range of vision and the immense scale of conflict. Central to this authorial dilemma is the question of the visual frame: how do you contain – within the written word – sight that resists containment and expression? The scale of the two world wars accentuated the representative problem of warfare. This thesis, by examining a wide range of World War One and World War Two literature, explores the varied literary responses to the topical relationship between sight and reality in wartime. It examines the war poetry of Wilfred Owen, Ford Madox Ford’s tetralogy Parade’s End, The Return of the Soldier by Rebecca West, Elizabeth Bowen’s The Heat of the Day, and Virginia Woolf’s novels Mrs Dalloway and Between the Acts alongside less well-known works such as David Jones’s prose-poem In Parenthesis, the two short stories ‘The Soldier Looks for His Family’ by John Prebble and ‘The Blind Man’ by D.H. Lawrence, as well as William Sansom’s collection of short stories Fireman Flower, and Louis Simpson’s war poetry. This thesis, by focussing on the inherent difficulties of reconciling perception and representation in war, interrogates the boundaries of sight and the limits of representation. The changing place of sight in writing from the two world wars is examined and the extent to which discourses of vision were shaped and developed, in the early decades of the twentieth century, by war experience is explored. The critical containment and categorisation of sight that often dominates readings of sight in texts from both world wars is questioned suggesting the need for a more flexible understanding of, and approach towards, sight.